SPORT-RELATED DYSTONIA – CURRENT STATE OF KNOWLEDGE IN DIAGNOSIS AND TREATMENT - Jan Puliński; Paulina Lewaśkiewicz; Klaudia Płudowska; Maksymilian Czarnota; Monika Rogowska; Karol Sikora; Wiktoria Boral; Marek Dróżdż; Alicja Czyszczoń; Wiktoria Marzec (International Journal of Innovative Technologies in Social Science, 2026)
Sports-related dystonia (SRD) is believed to arise as a consequence of repetitive motor activity, often involving tens of thousands of movement repetitions performed during high-level athletic training. Professional sports practice is characterized by prolonged physical exertion and the frequent execution of specific motor tasks, repeated hundreds or even thousands of times in pursuit of technical perfection. This intensive regimen may lead to both physical and mental fatigue, potentially resulting in overuse injuries. SRD has been most frequently described in golfers, runners, cricketers, basketball players, and gymnasts. Despite growing awareness of its clinical presentation, SRD remains a diagnostic and therapeutic challenge.The aim of this study is to provide a comprehensive review of the current state of knowledge regarding SRD, based on publications available in the PubMed database.A literature search was conducted using relevant keywords to identify scientific publications not older than five years, retrieved from academic databases. SRD represents a complex clinical syndrome that requires a multidisciplinary and individualized approach. The absence of specific diagnostic tests, combined with the variability and subtlety of symptoms, often results in significant diagnostic challenges. Effective treatment must be tailored to the specific symptom profile presented by each athlete, taking into account both motor and non-motor aspects of the condition. Currently, further research is needed to improve both the diagnostic criteria and therapeutic strategies for managing SRD. Early identification and preventive strategies—particularly in young athletes—should be emphasized. Educational efforts aimed at raising awareness of the potential career-threatening nature of SRD may facilitate earlier recognition of symptoms and help prevent premature discontinuation of athletic careers.Treatment of this disorder must be individualized and focused on the specific range of symptoms present in each athlete. Currently, further research on the diagnosis and therapeutic options for patients affected by this condition is necessary.